2020
DOI: 10.7759/cureus.7929
|View full text |Cite
|
Sign up to set email alerts
|

Combined Tibial Tubercle Fracture With Patellar Tendon Avulsion in an Adult: A Rare Case and Novel Fixation Technique

Abstract: Tibial tubercle avulsion fracture with simultaneous patellar tendon avulsion is a rare injury that has only ever been reported in adolescents; the diagnosis and management of this combined lesion has not been described in the adult population. A healthy 62-year-old male presented with acute knee pain and an inability to walk after a fall on ice. Radiographs demonstrated a displaced fracture of the tibial tubercle; patellar tendon integrity could not be verified by ultrasonography. Intraoperatively, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…In contrast, Bauer et al [17] reported five cases (23%) in their review of 22 patients with tibial avulsion fractures. This injury mainly affects adolescents (aged 13 to 16 years), which is consistent with the time of secondary ossification of the tibial tubercle apophysis; there is only a single report in the literature describing tibial tuberosity and patellar tendon avulsion in an adult patient [18].…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, Bauer et al [17] reported five cases (23%) in their review of 22 patients with tibial avulsion fractures. This injury mainly affects adolescents (aged 13 to 16 years), which is consistent with the time of secondary ossification of the tibial tubercle apophysis; there is only a single report in the literature describing tibial tuberosity and patellar tendon avulsion in an adult patient [18].…”
Section: Discussionsupporting
confidence: 55%
“…Tibial tuberosity fractures in adults due to direct trauma have already been reported, and direct trauma may be one of the mechanisms that can cause fractures in adults. 5 , 6 , 9 The fracture of our patient was also caused by direct trauma, and the characteristics of the fracture were different from avulsion fractures. It is known that when tibial tuberosity avulsion occurs, rotation of the bone fragment is followed.…”
Section: Discussionmentioning
confidence: 72%
“… 2 Therefore, TTF in adults are rare, and only a few cases have been reported, including cases in which fractures were caused by direct trauma. 1 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Avulsion fracture of the tibial tubercle is also a rare injury, more so with an associated patellar ligament rupture, which occurs most commonly in athletic adolescents due to an open physis [ 2 ] [ 3 ]. The first reported case was identified by Mayba in 1982 during which the mechanism of injury was theorized to occur through significant and continued contraction of the quadriceps muscle with a fixed foot or an external force causing contraction [ 3 ] [ 10 ]. The injury can present with a gap along the patella ligament and significant limitations in the extensor mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Tibial avulsion fractures are mostly seen in adolescents but are rare in adults [ 2 ]. Tibial avulsion fractures are associated with a patellar ligament rupture, and its treatment involves open reduction and internal fixation using screws, wires, or plates [ 2 ][ 3 ]. However, chronic injuries may require reconstruction of the patellar tendon due to marked deformity and limitations in motion [ 4 ][ 5 ].…”
Section: Introductionmentioning
confidence: 99%